Application of Oxide and Chalcogenide Semiconductor Films in Photoelectrochemical Reduction Reactions - de Araújo, Moisés A.; Brito, Juliana F. de [UNESP]; Silva, Mariana C.; Costa, Magno B.; Mascaro, Lucia H. (Springer Nature, 2025)
The study of semiconductorSemiconductor materials is traced back to 1833, when Michael Faraday first reported the temperatureTemperature dependence of electrical conductivityElectrical conductivity of silver sulfideSilver sulphide. Since then, substantial development of semiconductorSemiconductor theory has been achieved over the years. SemiconductorSemiconductor materials have been employed in a broad range of applicationsApplication, including solar energy harvestingSolar energy harvesting using photoelectrochemical (PEC) cellsPhotoelectrochemical (PEC) cells to generate fuelsFuelsuch asSolar-driven hydrogen gas generationhydrogen gasHydrogen gas. Compared to the currentCurrentsourceSource of energyEnergy, which is fossil fuelsFossil fuel, hydrogen gasHydrogen gas stands out as a cleanClean and sustainableSustainablefuelFuel. PEC cellsPhotoelectrochemical (PEC) cells can also be used to reduce carbon dioxideCarbon dioxide (CO2) or nitrogen gasNitrogen gas to chemicalChemical commodities. In all these cases, it is possible to observe the study of an unbelievable amount of different advanced semiconductorSemiconductor materials. In lightLight of the technological importance of semiconductorSemiconductor materials, this chapter presents the recent advancements in chalcogenideChalcogenide, (such as sulfides and selenidesSelenide), and oxideOxide-basedChalcogenide semiconductorssemiconductorSemiconductor materials used in the applicationsApplicationof PEC cellsPhotoelectrochemical (PEC) cells. Moreover, the technological relevance of such materials, especially with regard to their applicationsApplicationin PEC cellsPhotoelectrochemical (PEC) cells, is discussed in order to stimulate an improvement in the design of new advanced semiconductorSemiconductor materials.